2009
DOI: 10.1038/nsmb.1625
|View full text |Cite
|
Sign up to set email alerts
|

Structural evidence for consecutive Hel308-like modules in the spliceosomal ATPase Brr2

Abstract: Brr2 is a DExD/H-box helicase responsible for U4/U6 unwinding during spliceosomal activation. Brr2 contains two helicase-like domains, each of which is followed by a Sec63 domain with unknown function. We determined the crystal structure of the second Sec63 domain, which unexpectedly resembles domains 4 and 5 of DNA helicase Hel308. This, together with sequence similarities between Brr2’s helicase-like domains and domains 1–3 of Hel308, led us to hypothesize that Brr2 contains two consecutive Hel308-like modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
155
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(162 citation statements)
references
References 62 publications
6
155
1
Order By: Relevance
“…The S1087L RP33 exchange in human Brr2 reduces RNA affinity as well as ATPase and helicase activities 51 and RP33-like N1104L and R1107L exchanges in yeast Brr2 are associated with reduced ATPdependent U4/U6 unwinding in tri-snRNP preparations. 60 Mutation of a Brr2 element equivalent to the Hel308 separator loop resulted in reduction or loss of cell viability, 41,52 in line with a similar duplex disruption mechanism as in Hel308. However, in a yeast U4/U6 U5 tri-snRNP structure, 12 Brr2 is loaded on the U4/U6 di-snRNA with the putative separator loop distant from the U4/U6 duplex portion to be unwound and instead with an edge of the RecA2 domain abutting the end of this duplex region (Fig.…”
Section: Multiple Layers Of Helicase-associated Domains In Brr2mentioning
confidence: 89%
See 3 more Smart Citations
“…The S1087L RP33 exchange in human Brr2 reduces RNA affinity as well as ATPase and helicase activities 51 and RP33-like N1104L and R1107L exchanges in yeast Brr2 are associated with reduced ATPdependent U4/U6 unwinding in tri-snRNP preparations. 60 Mutation of a Brr2 element equivalent to the Hel308 separator loop resulted in reduction or loss of cell viability, 41,52 in line with a similar duplex disruption mechanism as in Hel308. However, in a yeast U4/U6 U5 tri-snRNP structure, 12 Brr2 is loaded on the U4/U6 di-snRNA with the putative separator loop distant from the U4/U6 duplex portion to be unwound and instead with an edge of the RecA2 domain abutting the end of this duplex region (Fig.…”
Section: Multiple Layers Of Helicase-associated Domains In Brr2mentioning
confidence: 89%
“…In contrast, in DEAH/RHA helicases an element equivalent to the separator loop (termed "5 0 HP") has been suggested to mainly control access to the single-stranded RNA binding site. 58,59 Comparative modeling 41,51,52 and a recent electron cryomicroscopic (cryo-EM) structure of a yeast U4/U6 U5 trisnRNP 12 showed that Brr2 engages its U4/U6 di-snRNA substrate in a similar manner as Hel308. A single-stranded region of the U4 snRNA is threaded through the central tunnel of the NC between the RNA-binding motifs of the RecA and HB domains, with 3 0 -portions of the RNA extending toward the CC (Fig.…”
Section: Multiple Layers Of Helicase-associated Domains In Brr2mentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the Prp8-CTR facilitates the binding of the Brr2/Prp8-CTR complex to U4/U6 in yeast. 41 In this current study, we have identified a potentially pathogenic mutation, p.R1779H, which is located between the second helicase CTR and sec-63 domains. It is the first candidate mutation found in the hel308-II module for RP.…”
Section: Discussionmentioning
confidence: 99%